A narrative hermeneutical adventure: Seafarers and their complex relationship with their families - Viljoen, Chris J. (HTS teologiese studies, 2012)
This research project is an attempt to develop a rich understanding about the relationship between seafarers and their families by means of a conversational construction between a number of co-researchers. In order to do this, the question that is explored is: How can there be a better understanding of the lives, the circumstances and the problems that seafarers are experiencing in the relationship with their families? The answer put forward in this research is that this can be accomplished through a narrative approach guided by the ABDCE formula which applies the metaphor of story writing to research. The research was motivated by pastoral and missionary concerns. The epistemologies that informed this research were social constructionism, the narrative approach and postfoundationalism with its emphasis on the interdisciplinary approach. In this article the main character for this research was a seafarer called John1 from Nigeria who was brought into conversation with a number of other co- researchers. The understanding that was developed found that the career choice of seafarers creates problems in their relationship with their family because they become in a sense strangers and outsiders to their loved ones. On the other hand seafarers are empowered, many times through their faith, to handle the challenges of their career, in addition to which this profession offers opportunities that would otherwise not have been possible. The relationship between a seafarer and his or her family was described as a complex one and thin, superficial and stereotypical conclusions were hopefully in the process deconstructed.